Synergistic Effect of Doxorubicin and siRNA-Mediated Silencing of Mcl-1 Using Cationic Niosomes against 3D MCF-7 Spheroids - Supusson Pengnam; Samarwadee Plianwong; Prasopchai Patrojanasophon; Widchaya Radchatawedchakoon; Boon-ek Yingyongnarongkul; Praneet Opanasopit; Purin Charoensuksai (MDPI AG, 2021)
Chemotherapy is a vital option for cancer treatment; however, its therapeutic outcomes are limited by dose-dependent toxicity and the occurrence of chemoresistance. siRNAs have emerged as an attractive therapeutic option enabling specific interference with target genes. Combination therapy using chemotherapeutic agents along with gene therapy could be a potential strategy for cancer management, which not only improves therapeutic efficacy but also decreases untoward effects from dose reduction. In this study, a cationic niosome containing plier-like cationic lipid B was used to convey siRNA against anti-apoptotic mRNA into MCF-7 and MDA-MB-231 cells. Mcl-1 silencing markedly decreased the viability of MCF-7 cells and triggered apoptosis. Moreover, computer modeling suggested that the combination of doxorubicin (Dox) and Mcl-1 siRNA exhibited a synergistic relationship and enabled a dose reduction of each agent at 1.71 and 3.91 folds, respectively, to reach a 90% inhibitory effect when compared to single-agent treatments. Synergistic antitumor activity was further verified in a 3D spheroid culture which revealed, in contrast to single-agent treatment, the combination markedly decreased spheroid volume over time. Together, the combination therapy between Mcl-1 silencing and Dox exhibits a synergistic effect that may be exploited for novel breast cancer treatment.